Analysis of Language Functions Used in Luca Films - Ade, Rizkika Ade Ramadani (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
This researcher aims to analyze the function of language used by the main characters in Luca film. In this study, researcher used Jacobson's 1995 theory to analyze the function of language in Luca film in improving the function of language in understanding grammar. In addition, this study was designed to find out the types of language functions and the use of language functions by the main characters in title animated Luca film. This research methodology is qualitative research with taking note and table as the instrument.There are two steps in data collection, namely, primary data derived from audiovisual, namely Luca's film and secondary data taken from the internet and some relevant materials to support and complement the primary data sources. The results of the study found five functions of language consisting of 72 dialogues used by the main character in Luca's film. There were 28 dialogues with (39%) of the expressive function, 16 dialogues with (22%) referred to the directive, 4 dialogues with (6%) represented poetic, 3 dialogues with (4%) pointed to phatic, and 21 dialogues with (29%) indicated referential.